2020
DOI: 10.1109/led.2020.2997319
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Fabricated Reconfigurable FET With Two Symmetric and High-Current On-States

Abstract: We demonstrate a top-down fabricated reconfigurable field effect transistor (RFET) based on a silicon nanowire that can be electrostatically programmed to pand n-configuration. The device unites a high symmetry of transfer characteristics, high on/off current ratios in both configurations and superior current densities in comparison to other top-down fabricated RFETs. Two NiSi2/Si Schottky junctions are formed inside the wire and gated individually. The narrow omega-gated channel is fabricated by a repeated Si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…[31] Further, the gate and Schottky contact metal work functions and the oxide-induced compressive stress to the Schottky junction could be adjusted to lift the asymmetry of the injection barriers for holes and electrons. [13] Importantly, the possibility of changing the configuration of each transistor within a circuit enables a reconfiguration of its specific logic functions during operation. [32] Further, the bidirectional nature of reconfigurable transistors is a clear advantage for flexible and adaptive circuit design, as equivalent results can be obtained by swapping the signals between source/drain and V PG /V CG .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] Further, the gate and Schottky contact metal work functions and the oxide-induced compressive stress to the Schottky junction could be adjusted to lift the asymmetry of the injection barriers for holes and electrons. [13] Importantly, the possibility of changing the configuration of each transistor within a circuit enables a reconfiguration of its specific logic functions during operation. [32] Further, the bidirectional nature of reconfigurable transistors is a clear advantage for flexible and adaptive circuit design, as equivalent results can be obtained by swapping the signals between source/drain and V PG /V CG .…”
Section: Resultsmentioning
confidence: 99%
“…With the use of Si channels and Ni x Si 1-x contacts various concepts with two or more independent gates have been proven experimentally. [8][9][10][11] Remarkably, symmetry in the output characteristics of p-and n-operation has been reached by the use of strain engineering both on bottom-up [12] and top-down Si nanowire RFETs [13] . Despite those outstanding efforts it has been noted, that the enhancement of the drive current and the reduction of dynamic power consumption strongly scales with the reduction of the respective Schottky barrier heights for electrons and holes.…”
mentioning
confidence: 99%
“…This is particularly detrimental to the PGAS mode, leading to a complete loss of noise margin. However, concerning the PGAD mode, it has been shown that highly scaled devices with a short screening length λ (representing the characteristic length on which potential variations are being screened [19], [20]) can also exhibit a linear output characteristic at room temperature due to the strongly increased tunneling probability through the Schottky barrier [8], [21].…”
Section: Device Characterizationmentioning
confidence: 99%
“…Recently, reconfigurable field-effect transistors (RFETs) have attracted increasing attention because they utilize electrostatic doping to create virtual n-/p-regions avoiding dopant-related issues. Moreover, they can be tuned to operate as n-/p-transistors with unipolar device operation similar to conventional MOSFETs [4]- [8]. Previous work using trigates [4], [5], i.e., two gates for creating virtual source/drain regions and the third one for ON/OFF switching, has demonstrated reconfigurable devices with high I ON /I OFF ratio and steep switching behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation